PENGELOLAAN MODAL MANUSIA DALAM KAITANNYA DENGAN MANAJEMEN KINERJA - Amanda Setiorini (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
Globalization changes the business environment, which demands change from every business organization involved, to succeed in the new environment. For that purpose, human resource management needs to be directed to the development of human capital, which assumes employees as assets, not costs, for the company. The implication is that management needs to recognize each of its employees in order to maximize their potential and manage it to be a competitive advantage. This is where performance management plays a very important role.